12 anathematisms of St. Cyril of Alexandria and the Christology of the Armenian Church - Arthur Matevosyan (Banber Arevelagitut'yan Instituti)
It is well known that the Christology of the Armenian Church is based on the Christological teaching of St. Cyril of Alexandria. Following St. Cyril, the Armenian Church confirms the invariability and perfection of divine and human natures in Christ. The hypostatic union of Christ does not lead to a change or amalgamation of natures. It admits the union of Christ with God the Father in deity and with us in humanity. Jesus Christ, the only begotten Son of God, is a perfect God and a perfect man, begotten before the ages from the Father according to deity, and for our salvation from Mary the Virgin according to humanity. And therefore, there is one nature of God the Word incarnate, revered together with His flesh in one worship. This is what the Armenian Church has believed since the 5th century to date. This article will examine the connection of 12 anathematisms contained in the letter of St. Cyril of Alexandria to Nestorius with the Christological teaching of the Armenian Church.